Analisis Tema Fantasi Komentar Donasi Palestina Pada Akun Youtube Nusantara Palestina Center - Susilawati, Lusi; Christin, Maylanny (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research aims to examine the influence of actors' positions in communication networks and the role of fantasy themes in Palestinian donation comments on the Nusantara Palestine Center YouTube channel. Employing social network analysis through Labspolsys and Gephi 0.10, the study focuses on the video titled "Extraordinary: Indonesian Citizens Finally Provide Clean Water Assistance for Palestine." The principal findings indicate that key actors such as @Rio_naldo, @Arifhidayat26190, @Anonymous5580, and @Vinijulvia exhibit significant capabilities in disseminating information. These actors contribute to the analysis of fantasy themes that reflect aspirations and values, including justice, freedom, solidarity, hope, change, and religiosity. The results suggest that fantasy themes in comments can shape public perceptions of social movements and bolster support. However, this research is limited in its ability to generalize findings to a broader population. In conclusion, this study sheds light on the role of fantasy themes in influencing narratives and perceptions of Palestinian donation social movements on digital platforms such as YouTube